In conversation W.V. Quine. (Philosophy International, 1994)
This program is an overview of Professor Quine's major philosophical doctrines and his comments on how he views these doctrines now. The areas considered include his early association with logical positivism, his scepticism about meaning, his stance on epistemology and ontology and his characterization of philosophy as a part of science.